Brain Drain: Rural Poverty and the Quebecois Zombie Film. Issue 1 (1st January 2021) - MacLeod, George
Abstract: Robin Aubert's 2017 film Les Affamés is a zombie genre film, set in an unspecified region of rural Quebec. The first Quebecois addition of note to the zombie film genre, Les Affamés follows the few remaining humans who have avoided contamination from their infected, flesh-eating pursuers. The rustic setting provides a haunting backdrop as the protagonist, a bearded science-fiction devotee named Bonin, and his five companions, attempt to flee through the woods to safety, pursued by a screaming, blood-thirsty horde of their former friends and neighbors. Les Affamés functions in large part as an allegory for rural poverty and economic isolation. Decaying farmhouses, rusting tractors, and an abandoned mine are just a few of the iconic images that invoke the real-world struggles of once-healthy agricultural and mining communities in a twenty-first-century neo-liberal economy. This paper will focus in particular on the zombie as an avatar for Quebecois and, more broadly, North American rural decay, noting how Aubert uses a zombie virus as an allegory for depopulation and economic marginalization. Indeed, the Affamés of the film's title also suggest the ravenous appetites of a capitalist system which, like the film's titular flesh-eating monsters, appears insatiable.